'The adherent taints of civilisation': entangled artefacts and the Queensland Museum, c.1880–1920. Issue 4 (2nd October 2019) - Burden, Gemmia
Abstract: This article explores the presence of entangled artefacts (traditional Aboriginal items that incorporated European technologies), analysing how they were used in the Queensland Museum over the late nineteenth and early twentieth centuries. Important objects of late colonial and post-Federation Aboriginal societies, these items made their way into the Museum's collections yet were excluded from displays. While they represent cultural fluidity and adaptation to changing and often challenging environments, I examine how they were interpreted at or near the time of their collection, and the ways in which the concept of authenticity was employed to marginalise them from displays. Exploring their contemporary interpretation provides a lens through which to analyse the broader institutional construction and representation of 'Aboriginality' over this period, which was narrated through the Museum's key exhibit, the Aboriginal camp diorama.